2011
DOI: 10.1128/aac.01606-10
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of E-101 Solution against Acinetobacter baumannii Isolates from U.S. Military Personnel

Abstract: We evaluated the in vitro and in vivo activity of a novel topical myeloperoxidase-mediated antimicrobial, E-101 solution, against 5 multidrug-resistant Acinetobacter baumannii isolates recovered from wounded American soldiers. Time-kill studies demonstrated rapid bactericidal activity against all A. baumannii strains tested in the presence of 3% blood. The in vitro bactericidal activity of E-101 solution against A. baumannii strains was confirmed in a full-thickness excision rat model. Additional in vivo studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Comparative MIC activities against MRSA (ATCC 43300) and E. coli (ATCC 25922) were determined using a modified broth microdilution method based on CLSI M7 guidelines (5, 30). Modifications included diluting enzyme solutions containing pMPO in double-strength cation-adjusted Mueller-Hinton broth (CAMHB).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative MIC activities against MRSA (ATCC 43300) and E. coli (ATCC 25922) were determined using a modified broth microdilution method based on CLSI M7 guidelines (5, 30). Modifications included diluting enzyme solutions containing pMPO in double-strength cation-adjusted Mueller-Hinton broth (CAMHB).…”
Section: Methodsmentioning
confidence: 99%
“…Selective MPO binding results in selective microbicidal action with minimal bystander damage. In vivo and in vitro studies have shown that E-101 solution exerts potent and broad-spectrum microbicidal action against Gram-positive and Gram-negative bacteria, including multidrug-resistant pathogens (47).…”
Section: Introductionmentioning
confidence: 99%
“…The recognition of an ever-dwindling arsenal of antimicrobial agents effective against an expanding population of MDR A. baumannii in military patients has led to the assessment of novel topical bactericidal formulations (E-101 myeloperoxidase solution), modalities of delivery (colistin-impregnated beads) and the evaluation of hitherto underutilised antibiotics (the aminoglycoside arbekacin) in this group [111][112][113].…”
Section: Susceptibility and Resistance In The Militarymentioning
confidence: 99%
“…Previous studies using the partial full-thickness pig wound model have shown that topical application of E-101 solution to surgical wounds does not impair subsequent wound healing (16). Furthermore, E-101 solution has demonstrated in vivo efficacy in wholeanimal models of surgical infection prevention (17,18).…”
mentioning
confidence: 99%